Quantitative analysis and pharmacokinetic study of a novel diarylurea EGFR inhibitor (ZCJ14) in rat plasma using a validated LC-MS/MS method - Zuo Sai-Jie; Cheng Xiao-Liang; Liu Dong-Zheng; Feng Wei-Yi; Cao Yong-Xiao; Zhang San-Qi (Acta Pharmaceutica)
1-(4-(Pyrrolidin-1-yl-methyl)phenyl)-3-(4-((3-(trifluoromethyl) phenyl)amino)quinazolin-6-yl)urea (ZCJ14), a novel epidermal growth factor receptor (EGFR) inhibitor, with diarylurea moiety, displays anticancer effect. In the present study, an LCMS/MS method was established to determine the concentration of ZCJ14 in rat plasma. Furthermore, the method was applied to investigate the pharmacokinetic characteristics of ZCJ14. Chromatographic separation of ZCJ14 and internal standard (IS) [1-phenyl-3-(4-((3-(trifluoromethyl)phenyl)amino) quinazolin-6-yl)urea] was accomplished by gradient elution using the Kromasil C18 column. The selected reaction monitoring transitions were performed at m/z 507.24→436.18 and 424.13→330.96 for ZCJ14 and IS, resp. The established method was linear over the concentration range of 10–1000 ng mL−1. The intra- and inter-day precisions were < 11.0 % (except for LLOQ which was up to 14.3 %) and the respective accuracies were within the range of 87.5–99.0 %. The extraction recovery and matrix effect were within the range of 88.4–104.5 % and 87.3–109.9 %, resp. ZCJ14 was stable under all storage conditions. The validated method was successfully applied to the pharmacokinetic study of ZCJ14 in rats, and the pharmacokinetic parameters have been determined. The oral bioavailability of ZCJ14 was found to be 46.1 %. Overall, this accurate and reliable quantification method might be useful for other diarylurea moiety-containing drugs.